2014
DOI: 10.3758/s13415-014-0327-2
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in reading: Dissociation of happiness and positivity

Abstract: The hierarchical emotion model proposed by Panksepp (1998) predicts that affective processing will rely on three functionally and neuroanatomically distinct levels, engaging subcortical networks (primary level), the limbic system (secondary level), and the neocortex (tertiary level). In the present fMRI study, we manipulated happiness and positivity, which are assumed to rely on secondary-and tertiary-level processes, respectively, to test these assumptions in a word recognition task. In accordance with the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 54 publications
(118 reference statements)
4
44
0
Order By: Relevance
“…Nevertheless, these results fit well with the evolutionary and appraisal accounts of aesthetic emotions discussed in the “Introduction” and also with data from recent neurocognitive studies using either lexical or VDTs (Briesemeister et al, 2014, 2015; Kuhlmann et al, 2016) and thus are further (computational) evidence for our specific hypothesis stated in the “Introduction.” Together these results suggest that valence is indeed a compound superfeature neuronally computed at the so-called tertiary (i.e., neocortical) level of affective processing according to Panksepp’s (1998) hierarchical theory of emotions. In contrast, joy/happiness and disgust are more basic and central affective responses likely computed at the secondary level (i.e., the limbic system).…”
Section: Stepwise Modeling Approachsupporting
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, these results fit well with the evolutionary and appraisal accounts of aesthetic emotions discussed in the “Introduction” and also with data from recent neurocognitive studies using either lexical or VDTs (Briesemeister et al, 2014, 2015; Kuhlmann et al, 2016) and thus are further (computational) evidence for our specific hypothesis stated in the “Introduction.” Together these results suggest that valence is indeed a compound superfeature neuronally computed at the so-called tertiary (i.e., neocortical) level of affective processing according to Panksepp’s (1998) hierarchical theory of emotions. In contrast, joy/happiness and disgust are more basic and central affective responses likely computed at the secondary level (i.e., the limbic system).…”
Section: Stepwise Modeling Approachsupporting
confidence: 89%
“…Based on previous empirical and theoretical work from our group, we submitted the hypothesis that the main factor used in the investigation of EADs, i.e., stimulus valence, is a semantic superfeature resulting from a yet unknown integration of experiential and distributional data, at least partially represented in associative activation patterns of affective-semantic networks starting out in parts of the limbic system (Ponz et al, 2013; Briesemeister et al, 2014, 2015; Jacobs et al, 2015; Kuhlmann et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Briesemeister, Kuchinke, and Jacobs (2014) found that the emotional category of words (happiness) affected the early N1 ERP component, whereas the valence of the words (positivity) affected later ERP components-an N400-like component and the late positive complex. Discrete categories and affective dimensions were also found to be dissociable in the brain, as suggested by different patterns of brain activation in response to, for example, happiness versus the overall positivity of words (Briesemeister, Kuchinke, Jacobs, & Braun, 2015). Examples of standardized sets of single words include the Affective Norms for English Words (ANEW; M. M. Bradley & Lang, 1999) and associated discrete norms (Stevenson et al, 2007), the Berlin Affective Word List (Võ et al, 2009) and associated discrete norms for nouns (e.g., DENN-BAWL; Briesemeister, Kuchinke, & Jacobs, 2011), the Leipzig Affective Norms for German (Kanske & Kotz, 2010), and the Nencki Affective Word List .…”
mentioning
confidence: 99%
“…In particular, Briesemeister et al (2014) investigated the temporal dynamics of affective processing using event related potentials (ERPs), finding that discrete-emotion effects occurred earlier than dimensional effects. In a similarly oriented fMRI study, Briesemeister et al (2015) reported that the brain areas affected by the manipulation of positivity were not the same as those affected by the manipulation of happiness. According to these authors, such results cannot be accounted for by either discrete-emotion theories or dimensional theories alone.…”
mentioning
confidence: 99%